Adenosine receptors differentially mediate enteric glial cell death induced by Clostridioides difficile Toxins A and B - Costa, Deiziane V. S.; Shin, Jae H.; Goldbeck, Sophia M.; Bolick, David T.; Mesquita, Flavio S.; Loureiro, Andrea V.; Rodrigues-Jesus, Mônica J.; Brito, Gerly A. C.; Warren, Cirle A. (Frontiers in Immunology, 2023)
Increased risk of intestinal dysfunction has been reported in patients after Clostridioides difficile infection (CDI). Enteric glial cells (EGCs), a component of the enteric nervous system (ENS), contribute to gut homeostasis. Previous studies showed that adenosine receptors, A2A and A2B, modulate inflammation during CDI. However, it is unknown how these receptors can modulate the EGC response to the C. difficile toxins (TcdA and TcdB). We investigated the effects of these toxins on the expression of adenosine receptors in EGCs and the role of these receptors on toxin-induced EGC death. Rat EGCs line were incubated with TcdA or TcdB alone or in combination with adenosine analogues 1h prior to toxins challenge. After incubation, EGCs were collected to evaluate gene expression (adenosine receptors and proinflammatory markers) and cell death. In vivo, WT, A2A, and A2B KO mice were infected with C. difficile, euthanized on day 3 post-infection, and cecum tissue was processed. TcdA and TcdB increased A2A and A3 transcripts, as well as decreased A2B. A2A agonist, but not A2A antagonist, decreased apoptosis induced by TcdA and TcdB in EGCs. A2B blocker, but not A2B agonist, diminished apoptosis in EGCs challenged with both toxins. A3 agonist, but not A3 blocker, reduced apoptosis in EGCs challenged with TcdA and TcdB. Inhibition of protein kinase A (PKA) and CREB, both involved in the main signaling pathway driven by activation of adenosine receptors, decreased EGC apoptosis induced by both toxins. A2A agonist and A2B antagonist decreased S100B upregulation induced by C. difficile toxins in EGCs. In vivo, infected A2B KO mice, but not A2A, exhibited a decrease in cell death, including EGCs and enteric neuron loss, compared to infected WT mice, reduced intestinal damage and decreased IL-6 and S100B levels in cecum. Our findings indicate that upregulation of A2A and A3 and downregulation of A2B in EGCs and downregulation of A2B in intestinal tissues elicit a protective response against C. difficile toxins. Adenosine receptors appear to play a regulatory role in EGCs death and the proinflammatory response induced by TcdA and TcdB, and thus may be potential targets of intervention to prevent post-CDI intestinal dysmotility.